Assessment of energy expenditure using doubly labeled water, physical activity by accelerometer and reported dietary intake in Japanese men with type 2 diabetes: A preliminary study. Issue 2 (15th October 2018) - Yoshimura, Eiichi; Ohkawara, Kazunori; Ishikawa‐Takata, Kazuko; Yamada, Satoru; Tokui, Mikiya; Funae, Osamu; Takimoto, Hidemi; Katsukawa, Fuminori
Abstract: The aim of the present study was to determine the total energy expenditure, physical activity and dietary intake of men with type 2 diabetes mellitus and control participants without type 2 diabetes mellitus who were matched for age and body mass index. The participants in the present study were 12 well‐controlled type 2 diabetes mellitus patients and 10 controls, aged 40–75 years, with a body mass index <30 kg/m 2 . Total energy expenditure under free‐living conditions was assessed using the doubly labeled water method, and physical activity was measured using a triaxial accelerometer. Dietary intake was assessed using a self‐recorded food intake diary during the measurement period. Participants were instructed to record their dietary intake over 3 days, including 2 weekdays. Total energy expenditure was not significantly different between the groups ( P = 0.153), nor were energy ( P = 0.969) or macronutrient intakes. In conclusion, when age and body mass index are matched, total energy expenditure and self‐reported energy intake are not significantly different between type 2 diabetes mellitus patients and healthy controls. Abstract : The aim of this study was to investigate differences in total energy expenditure using doubly‐labeled water, physical activity by accelerometer, and reported dietary intake between patients with type 2 diabetes mellitus and those without type 2 diabetes mellitus. Total energy expenditures, physical activity, and energy intakes were not significantly different between T2DM patients and healthy controls.